Isolation and preliminary characterization of temperature-sensitive mutants of Newcastle disease virus. - Tsipis, J E (1976)
Temperature-sensitive (ts) mutants of Newcastle disease virus have been isolated and characterized genetically (complementation), biochemically (RNA synthesis) and biologically (fusion from within and hemadsorption). Fifteen of these mutants have been divided into five complementation groups. Groups A (five mutants) and E (one mutant) are ts for RNA synthesis (RNA-) as well as for the other functions. Group B contains four RNA+ mutants of which one is ts for fusion, one for hemadsorption and two for neither function. Group C contains one RNA+ mutant which is a poor cell fuser. Group D contains two RNA+ mutants which are ts for fusion. In addition, two noncomplementing mutants (group BC) fail to complement both group B and group C mutants while exhibiting complementation with mutants in groups A, D, and E.